2011
DOI: 10.1038/onc.2011.191
|View full text |Cite
|
Sign up to set email alerts
|

Tp53 deletion in B lineage cells predisposes mice to lymphomas with oncogenic translocations

Abstract: Inactivating Tp53 mutations are frequent genetic lesions in human tumors that harbor genomic instability, including B lineage lymphomas with IG translocations. Antigen receptor genes are assembled and modified in developing lymphocytes by RAG/AID-initiated genomic rearrangements that involve the induction of DNA double strand breaks (DSBs). Although TP53 inhibits the persistence of DSBs and induces apoptosis to protect cells from genomic instability and transformation, the development of spontaneous tumors har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
19
2
1
Order By: Relevance
“…VP and LP mice succumb to tumors at similar ages as Tp53 −/− , Lck-cre:Tp53 −/− mice, and Mb1-cre:Tp53 flox/flox mice. 32,33,36,44 In contrast to the aneuploid thymic lymphomas that arise in Tp53 −/− mice, we found that VP and LP mice developed lymphomas with aneuploidy or clonal translocations, including Ig or Tcrα/δ translocations. The distinct cancer phenotypes of these mice indicate that loss of Tp53 during embryogenesis, in cells before lymphocyte commitment, and/or in thymocytes masks development of lymphomas with oncogenic translocations in germline Tp53-deficient mice.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…VP and LP mice succumb to tumors at similar ages as Tp53 −/− , Lck-cre:Tp53 −/− mice, and Mb1-cre:Tp53 flox/flox mice. 32,33,36,44 In contrast to the aneuploid thymic lymphomas that arise in Tp53 −/− mice, we found that VP and LP mice developed lymphomas with aneuploidy or clonal translocations, including Ig or Tcrα/δ translocations. The distinct cancer phenotypes of these mice indicate that loss of Tp53 during embryogenesis, in cells before lymphocyte commitment, and/or in thymocytes masks development of lymphomas with oncogenic translocations in germline Tp53-deficient mice.…”
Section: Discussioncontrasting
confidence: 55%
“…4B and C). Since the c-myc oncogene on chromosome 15 is activated by Igh or Tcrα/δ translocations in mouse lymphomas, 40,44 we also used a c-myc probe to identify potential Igh;c-myc and Tcrα/δ;c-myc translocations in VP lymphoma no. 421 and LP lymphoma no.…”
Section: Conditional Inactivation Of Tp53 In Hscs or Thymocytes Causementioning
confidence: 99%
See 1 more Smart Citation
“…39 Cells were stained with antibodies against surface antigens in PBS with 3% FBS and then washed before flow cytometry. The antibodies used from BD PharMingen were: anti-TCRb (553172), anti-CD4 (553653), anti-CD8a (553033), anti-CD25 (552880), anti-CD117 (553356).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…33,36 Deficiency of p53 results in a higher incidence of lymphoid malignancies with chromosomal translocations, consistent with an important role for this tumor suppressor in eliminating cells at risk for aberrant DNA repair and malignant transformation. 33,[37][38][39][40][41] However, mechanisms must exist to ensure that p53 does not induce the death of all cells attempting to assemble antigen receptor genes.…”
Section: Rag Dsbs Activate a Unique Transcriptional Programmentioning
confidence: 99%